The orphan nuclear receptor COUP-TFII is required for angiogenesis and heart development - Pereira, Fred A. (Cold Spring Harbor Laboratory Press, 1999)
The embryonic expression of COUP-TFII, an orphan nuclear receptor, suggests that it may participate in mesenchymal–epithelial interactions required for organogenesis. Targeted deletion of the COUP-TFII gene results in embryonic lethality with defects in angiogenesis and heart development. COUP-TFII mutants are defective in remodeling the primitive capillary plexus into large and small microcapillaries. In the COUP-TFII mutant heart, the atria and sinus venosus fail to develop past the primitive tube stage. Reciprocal interactions between the endothelium and the mesenchyme in the vascular system and heart are essential for normal development of these systems. In fact, the expression of Angiopoietin-1, a proangiogenic soluble factor thought to mediate the mesenchymal–endothelial interactions during heart development and vascular remodeling, is down-regulated in COUP-TFII mutants. This down-regulation suggests that COUP-TFII may be required for bidirectional signaling between the endothelial and mesenchymal compartments essential for proper angiogenesis and heart development.